3D printing of Cordyceps flower powder. (17th July 2019) - Teng, Xiuxiu; Zhang, Min; Bhandri, Bhesh
Abstract: Cordyceps militaris is a fungus that has been used as a functional food in China because it contains many kinds of active components (such as cordycepin, polysaccharides, ergosterol, mannitol, etc.). Cordyceps flowers are dried and also available in powder form with poor rehydration behavior. Considering taste, mouthfeel and appearance of printed products, the optimal printing formulation (powder: water: isomaltose: oil = 10:10:3:1) was obtained through response surface methodology. The rheological properties of rehydrated powder were enhanced due to the lubricating action of oil and the moisture absorption by isomaltose, reducing the line breakage but still showed structural collapse. Fortunately, the disadvantages of the above formulation were overcome by the addition of 1% (w/w powder) gum. The new formulation (powder: water: isomaltose: oil: agar = 10:10:3:1:0.1) exhibited the best printing results and there was a little effect on cordycepin content through 3D printing technology. The effectiveness of this new formulation as a printing ink was confirmed by low‐field nuclear magnetic resonance, rheological and textural measurements. Practical applications: Cordyceps flowers and isomaltose contain many functional factors. 3D printing technology has the ability to design an appealing appearance, and capability of producing variety of textures by manipulating the internal structure. The combination of the two provides consumers with rich functional factors while attracting consumers to increase their acceptability of Cordyceps flowers. This study provides new ideas for other variety of food printing materials and demonstrates the shape development of foods by 3D printing. Abstract :